2019
DOI: 10.33963/kp.14963
|View full text |Cite
|
Sign up to set email alerts
|

Presence and characteristics of coronary artery fistulas among patients undergoing coronary angiography

Abstract: Background Coronary artery fistula is defined as a connection between one or more coronary artery and a heart chamber. aims The aim of the study was to determine the overall incidence of coronary artery fistulas in Polish patients undergoing diagnostic coronary artery angiography as well as the frequency of particular origin and draining sites. methods The data were obtained from the Polish National Registry of Invasive Cardiology Procedures among patients hospitalized between January 1, 2014 and December 31, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…Lim et al 10 demonstrated that there is a relation between CAFs, in particular in coronary to bronchial and pulmonary fistulas, and lung parenchymal abnormalities such as bronchiectasis or hypoplasia of the pulmonary vasculature. These findings could, in part, explain the high incidence of chronic obstructive disease in association with CAFs reported by Podolec et al 7 In conclusion, the relevance of the study by Podolec et al 7 lies in the amount of data described, and it provides useful information on prevalence and anatomy of CAFs. However, as all the studies on CAFs, it is a retrospective analysis, which cannot provide information on clinical significance and prognostic impact of CAFs.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…Lim et al 10 demonstrated that there is a relation between CAFs, in particular in coronary to bronchial and pulmonary fistulas, and lung parenchymal abnormalities such as bronchiectasis or hypoplasia of the pulmonary vasculature. These findings could, in part, explain the high incidence of chronic obstructive disease in association with CAFs reported by Podolec et al 7 In conclusion, the relevance of the study by Podolec et al 7 lies in the amount of data described, and it provides useful information on prevalence and anatomy of CAFs. However, as all the studies on CAFs, it is a retrospective analysis, which cannot provide information on clinical significance and prognostic impact of CAFs.…”
mentioning
confidence: 76%
“…For commercial use, please contact the journal office at kardiologiapolska@ptkardio.pl. Indications for coronary angiography in the study of Podolec et al 7 were stable coronary artery disease, acute coronary syndromes, cardiac arrest, congenital heart defects, and other indications. They found a higher prevalence of CAFs in the subgroup of patients submitted to coronary angiography for other indications.…”
mentioning
confidence: 99%
See 3 more Smart Citations